Effect of mammography imaging procedure on serum inflammatory and/or tumor marker levels učinak mamografskog postupka na serumske razine upalnih I/ili tumorskih biljega - (:unkn) unknown (My University, 2023)
SUMMARY – Mammography is one of the gold standard screening tests for breast cancer. The effects of mammography procedure on blood parameters are not known. This study aimed to inves-tigate whether the procedure-associated breast compression affects the widely and simultaneously performed blood measurements of C-reactive protein (CRP), carcinoembryonic antigen (CEA), and cancer antigen (CA) 15-3. According to breast ultrasound examination results, participants were di-vided into 3 groups as follows: group 1 (participants with breast mass size ≥20.0 mm, n=48); group 2 (participants with breast mass size 0.05, respectively). On the day of the mammographic imaging study, the optimal time of blood sampling for testing CRP, CEA and CA 15-3 levels in persons with a breast mass is before, but not after the mammographic imaging procedure. This issue requires additional detailed studies.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Blood tests; Breast cancer; Breast compression; C-reactive protein; Mammography; Tumor markers